Collection Development Service. Cataloguing. Indexing. Presentation. (Confluenţe Bibliologice, 2016)
In the article are speciﬁed core activities of the Collection Development Service. Cataloguing, Indexing, including databases, application programs used in library.
Keywords: databases; cataloging; electronic catalog; collection development service